Watch-and-wait approach following neoadjuvant chemo-radiotherapy for locally advanced rectal cancer: a retrospective single-center cohort study - Kalev, Georgi; Büttner, Sylvia; Zhan, Tianzuo; Hofheinz, Ralf-Dieter; Boda-Heggemann, Judit; Reißfelder, Christoph; Seyfried, Steffen; Vassilev, Georgi; Hardt, Julia (Journal of surgical oncology, 2024)
Background and Objectives The watch-and-wait (WW) strategy in patients after complete clinical response (cCR) following chemoradiotherapy for locally advanced rectal cancer (LARC) offers the option of organ preservation. The aim of this study was to assess the oncological outcomes of WW patients treated and followed up in a German referral cancer center. Methods In this retrospective study, we analyzed the clinical records of consecutive patients with LARC who underwent neoadjuvant radiotherapy/chemoradiotherapy at our institution between January 2020 and December 2023 and received non-operative management after cCR. Results A total of 30 patients undergoing WW for LARC were included. After a median follow-up of 17 months (SD = 10 months), local regrowth occurred in four patients (4/30, 13.3%), and one patient (1/30, 3.3%) developed distant metastasis. No predictor for tumor regrowth could be identified based on radiological findings at diagnosis, including cT4 and/or cN2, involvement of the mesorectal fascia, extramural vascular invasion or infiltration of the anal sphincter/levator. All patients with local regrowth were successfully surgically treated (R0 resection). Conclusion Nonoperative management for patients with cCR after neoadjuvant therapy for LARC proved to be safe. R0 resection was successfully achieved in all patients who underwent salvage surgery.
Gesehen am 31.03.2025